Japanese language, gender, and ideology : cultural models and real people - Okamoto, Shigeko; Shibamoto-Smith, Janet S. (Studies in language and gender., 2004)
A collection of articles by established as well as young scholars in Japanese language and gender studies. This volume brings together studies that advance our understanding of the relationship between Japanese language and gender, with particular focus on examining local linguistic practices in relation to dominant ideologies.